Asuhan Keperawatan Jiwa Pada Pasien Dengan Resiko Perilaku Kekerasan Di Wisma Flamboyan Rsj Prof. Dr. Hb Sa’anin Padang - Rini Refalina; Dwi Happy Anggia Sari; Vivi Yuderna; Ramaita . (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Risk of Violent Behavior is a condition where a person commits an act that can be physically dangerous, both to themselves and others, accompanied by uncontrolled rage, noise, and anxiety. Based on medical record data from Prof. HB. Sa'anin Mental Hospital Padang, the nursing diagnosis of Risk of Violent Behavior is still high, namely in 2023 there were 213 cases, in 2024 there were 138 cases, and in 2025 there were 159 cases. The purpose of this case study is to obtain an overview of the implementation of psychiatric nursing care for patients with Risk of Violent Behavior. The method used is a descriptive case study with a nursing process approach including assessment, diagnosis, intervention, implementation, and evaluation. Nursing actions are given through deep breathing exercises, hitting pillows, education on taking medication regularly, good verbal communication, and spiritual activities. The results show that patients are calmer, more cooperative, able to control anger, do not speak harshly, and are compliant in taking medication. It can be concluded that psychiatric nursing care is effective in reducing signs and symptoms of the risk of violent behavior. It is hoped that nurses and families will play an active role in preventing recurrence.